Methods, systems, and computer program products for determining an ammunition round count by resistive encoding - Cline, Zachary (2023)
The subject matter described herein includes methods, systems, and computer program products for determining an ammunition round count by resistive encoding. According to one embodiment, a system for providing an indication of a number of rounds of ammunition in a magazine of a firearm includes a follower for the rounds to rest upon, where the follower is internal to the magazine and pushes the follower and the rounds toward a mouth of the magazine to facilitate feeding the rounds into the firearm. The system also includes a resistive strip membrane potentiometer sensor arranged substantially along a length of the magazine that generates an output voltage when a first and a second circuit are connected by applying pressure to a surface of the sensor. The output voltage varies based on a position where the pressure is applied to the surface of the sensor and the first and second circuits are connected. A power source, such as a battery or AC/DC adapter, applies power to the system which contains a constant current source to generate and provide an input voltage to the resistive strip membrane potentiometer sensor. A wiper applies pressure to the surface of the sensor and connects the first and second circuits. The wiper is a non-conductive mechanism attached to the follower and configured to move along the length of the magazine corresponding to the resistive strip membrane potentiometer sensor. A round counter converts the output voltage generated by the resistive strip membrane potentiometer sensor into an indication of the number of rounds of ammunition in the firearm magazine ("round count data").